Effects of Phenyllactic Acid, Lactic Acid Bacteria, and Their Mixture on Fermentation Characteristics and Microbial Community Composition of Timothy Silage - Li, Ping; Lu, Yongxiang; Zhao, Man; Chen, Liangyin; Zhang, Changbin; Cheng, Qiming; Chen, Chao (Frontiers in Microbiology, 2021)
This study investigated the effects of phenyllactic acid, lactic acid bacteria and their mixture on fermentation characteristics and microbial community composition of timothy silage. The timothy silages were treated without (CK) or with phenyllactic acid (PL, 10 mg/kg fresh matter (FM) basis), lactic acid bacteria (LAB) inoculant (IN, a mixture of Lactobacillus plantarum and L.buchneri, 105 cfu/g FM) and their mixture (PI), and stored at ambient temperature (<15℃) in dark room for 60 days. Compared with CK, all treated-silages showed lower (P<0.05) levels of butyric acid and ammonia-N. Treatment with PL enhanced the crude protein preservation of silage by favoring the growth of L.curvatus and Saccharomyces cerevisiae and inhibition of lactic acid-assimilating yeast belonging to Issatchenkia during ensiling. In particular, treatment with PL advanced the productions of lactic acid and volatile fatty acid in IN-treated silage. Therefore, phenyllactic acid used as a new additive exhibited potential for improving silage fermentation when it combined with LAB inoculant during ensiling.